PNV J00444033+4113068: Early superhumps with 0.7 mag amplitude and non-red color. (16th September 2022) - Tampo, Yusuke; Isogai, Keisuke; Kojiguchi, Naoto; Uemura, Makoto; Kato, Taichi; Tordai, Tamás; Vanmunster, Tonny; Itoh, Hiroshi; Dubovsky, Pavol A; Medulka, Tomáš; Sano, Yasuo; Hambsch, Franz-Josef; et al.
Abstract: In the first days of WZ Sge-type dwarf nova (DN) outbursts, the 2 : 1 resonance induces a spiral arm structure in the accretion disk, which is observed as early superhumps in optical light curves. We reports on our optical observations of an eclipsing WZ Sge-type DN PNV J00444033+4113068 during its 2021 superoutburst using the 3.8 m Seimei telescope and through the Variable Star Network collaboration. The eclipse analysis showed that its orbital period was 0.055425534(1) d. Our observations confirmed early superhumps with an amplitude of 0.7 mag, the largest amplitude among known WZ Sge-type DNe. More interestingly, its early superhumps became the reddest around their secondary minimum, whereas other WZ Sge-type DNe show the reddest color around the early superhump maximum. The spectrum around the peak of the outburst showed two double-peaked emission lines of He ii 4686 Å and Hα with a peak separation of ≥700 km s −1, supporting a very high-inclination system. With the early superhump mapping, the unique profile and color of the early superhump are successfully reproduced by an accretion disk with a vertically extended double arm structure. Therefore, a large amplitude and a unique color behavior of the early superhumps in PNV J00444033+4113068 can be explained by the 2 : 1 resonance model along with other WZ Sge-type DNe.